Overcoming cultural constraints in translating English series: a case study of subtitling family guy into Arabic - Debbas, Manar; Haider, Ahmad S. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Subtitling and dubbing foreign animation in Arabic have been growing since TV screens reached Arab homes. This imposes stricter control and ethical supervision of the used language. This study examines the cultural constraints in subtitling the American animated sitcom Family Guy into Arabic. Family Guy addresses sensitive matters, such as sex, alcohol, religion, and politics, and so it is viewed with concern and caution in the Arab world. The researchers classified the cultural constraints in translation into three main categories: religious remarks, jokes & humour that revolve around proper nouns, and taboos. The analysis shows that the strategies used in translating religious remarks were scene deletion, words omission, and words omission with justifications. For jokes and humour, the translator opted for three strategies, namely, retain unchanged, retain unchanged with added guidance and retain unchanged with detailed explanation. Euphemistic expressions and word omission were the two strategies followed in translating taboos. The study concludes that the target audience has a vital role in determining the appropriate constraints on translation that go in line with their ideology and culture.